Experiment and Numerical Simulation on Creep Mechanical Behaviors of Mudstone under Unloading Condition. (4th May 2022) - Feng, Xudong
Abstract : The deep soft rock with complex occurrence conditions is easy to produce significant creep deformation under the influence of high in situ stress, high temperature, and disturbance, which has a great influence on the safety and long-term stability of structures with long service life, such as underground chambers and nuclear waste storage rooms. To study the creep effect of surrounding rock of deep chamber under the condition of excavation and unloading, creep tests of deep mudstone over 1000 meters in unloading confining pressure were carried out in this work. The experimental results show that high confining pressure has a significant inhibition effect on the creep behavior of rock, while high axial stress aggravates the creep behavior, which is manifested by the increase of creep deformation and the shortening of total creep time. When the axial stress is higher than the yield strength of the rock mass, the rock mass enters the tertiary creep stage (which is characterized by large deformation and instability failure in a short period of time). An improved nonlinear viscoelastic-plastic rock creep model, which can simulate three creep stages, is established (well verified). In addition, the creep deformation of surrounding rock after excavation is simulated based on this model, and the simulation results are consistent with the engineering practice: after 165 days of excavation, there is still a large deformation rate.